Decoding Inner Speech Using Electrocorticography: Progress and Challenges Toward a Speech Prosthesis - Martin, Stephanie; Iturrate, Iñaki; Millán, José del R.; Knight, Robert T.; Pasley, Brian N. (Frontiers in Neuroscience, 2018)
Certain brain disorders resulting from brainstem infarcts, traumatic brain injury, cerebral palsy, stroke and amyotrophic lateral sclerosis, limit verbal communication despite the patient being fully aware. People that cannot communicate due to neurological disorders would benefit from a system that can infer internal speech directly from brain signals. In this review article, we describe the state of the art in decoding inner speech, ranging from early acoustic sound features, to higher order speech units. We focused on intracranial recordings, as this technique allows monitoring brain activity with high spatial, temporal, and spectral resolution, and therefore is a good candidate to investigate inner speech. Despite intense efforts, investigating how the human cortex encodes inner speech remains an elusive challenge, due to the lack of behavioral and observable measures. We emphasize various challenges commonly encountered when investigating inner speech, and propose potential solutions in order to get closer to a natural speech assistive device.